Taste and smell disturbances in patients with chronic oral graft vs. host disease: An observational study - Boor, Marlou; Raber-Durlacher, Judith E.; Hazenberg, Mette D.; Rozema, Frederik R.; Laheij, Alexa M. G. A. (Frontiers in Oral Health, 2022)
Abstract Background: A common complication of allogeneic hematopoietic stem cell transplantation (alloHSCT) is chronic oral graft versus host disease (cGvHD). Oral cGvHD may present as mucosal lesions, salivary gland dysfunction and trismus. Moreover, taste and smell ability may be affected, but the prevalence, nature and severity of altered taste and smell function and their impact on quality of life (QoL) are understudied. Aim: To identify the prevalence, nature, and severity of taste and smell disturbances, their impact on QoL and to assess whether altered taste/smell ability is associated with oral mucosal cGvHD or hyposalivation. Materials and methods: AlloHSCT recipients who were transplanted at least 100 days ago and have been referred to the oral GVHD clinic of the Amsterdam UMC because of oral cGvHD-related oral complaints were eligible for participation in this cross-sectional study. Manifestations of oral mucosal cGvHD were scored (NIH oral cGvHD Activity Assessment tool), the unstimulated and stimulated salivary flow was measured, and objective taste and smell ability was evaluated (Taste strips & Sniffin’sticks). Subjective taste and smell alterations (Epstein scale), overall (EORTC QLQ-C30) and oral health-related QoL (EORTC QLQ-OH15 & OHIP-14) were assessed. Results: Objective reduced taste ability (hypogeusia) was identified in the majority of the 45 patients (68.9%), whereas 28.9% had hyposmia (reduced smell ability), and 11.1% had anosmia (complete loss of smell). However, only one third of patients (31.1%) reported severe taste alterations and 22% reported moderate taste alterations indicating that not all patients were aware of their altered taste sense. Taste/smell disturbances were not related to the presence of oral mucosal cGvHD or hyposalivation, yet they were associated with reduced oral health-related QoL. Conclusion: Taste and smell disturbances are prevalent among alloHSCT recipients and have a negative impact on QoL. Gaining more knowledge on the epidemiology and pathobiology of these complications and risk factors is mandatory as this could contribute to advances in supportive care interventions and improve alloHSCT recipients’ QoL.